(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In the article, all innovative innovations in education for children serve to increase the effectiveness of teaching. The appropriate use of new pedagogical technologies in preschool education increases the effectiveness of teaching. The article describes pedagogical technologies.